Feasibility of magnetic resonance elastography for the pancreas at 3T. Issue 2 (7th July 2015) - Itoh, Yohei; Takehara, Yasuo; Kawase, Toshihiro; Terashima, Kenichi; Ohkawa, Yoshihisa; Hirose, Yuko; Koda, Ai; Hyodo, Naoko; Ushio, Takasuke; Hirai, Yuki; Yoshizawa, Nobuko; Yamashita, Shuhei; et al.
Abstract : Purpose: 1) To assess the usefulness of an elastic belt bracing the upper abdomen for reducing the miscalculated areas of the pancreas on 3.0T magnetic resonance elastography (MRE); 2) to test whether MRE can detect difference of stiffness between normal pancreas and the focal pancreatic diseases. Materials and Methods: Using an initial eight normal volunteers, miscalculated areas were compared between MRE with the elastic belt and without the belt on 3.0T MRI. Then, using the belt, MRE of the normal pancreas was measured using 14 volunteers and 11 patients with focal pancreatic lesions. Results: The median (95% confidence interval [CI]) percentages of correctly calculated areas were 57.4% (32.9–63.0) with the elastic belt and 35.3% (11.4–60.4) without the belt ( P = 0.0078). The stiffness of each pancreatic segment of the normal volunteers (mean ± SE) was 2.37 ± 0.16 kPa for the head, 2.46 ± 0.17 kPa for the body, and 2.58 ± 0.26 kPa for the tail. The stiffness of seven pancreatic cancers was 6.06 ± 0.49 kPa, which was higher than the overall pancreatic stiffness of the normal volunteers (2.47 ± 0.11 kPa, P < 0.0001). Stiffness of the pancreatic lesions in the head of 6.03 ± 0.42 kPa, body of 5.57 ± 0.82 kPa, and tail of 5.9 ± 1.9 kPa were also higher than those of corresponding segments of the normal volunteers ( P = 0.0011, 0.0029, and 0.029, respectively). Conclusion: With the elastic belt, miscalculation of the pancreatic stiffness was reduced. MRE showed differences of stiffness between normal pancreas and pancreatic lesions. J. Magn. Reson. Imaging 2016;43:384–390.